Cost efficiency in the production of crop products as a factor of formation of competitiveness in international markets - Shyian, Nataliia; Kovalyova, Olena; Moskalenko, Valentyna; Murenets, Irina; Kniaz, Sviatoslav (Ceres Publishing House, 2023)
It was established that there is a close relationship between the level of costs and the yield of crops. At the same time, there is a manifestation of the law of diminishing returns, which leads to a drop in the level of profitability and profitability of production with an increase in the level of costs. The construction of the dependence of the paired regression of productivity-costs-profit, productivity-costs-level of profitability was carried out. The value of the coordinates of the point of intersection of the dependence of the profit and costs on the productivity of wheat, corn for grain, and sunflower was determined. The economic meaning of the obtained coordinates will be that with a given increase in X (yield), the amount of profit per 1 ha of the sown area will exceed costs per unit of land area following the established dependencies. It is proposed to determine the economic efficiency index of crop production intensity. The calculation of this index made it possible to establish that it was on average 4.506 for sunflower, 2.500 for wheat, and 2.102 for corn. For the first time, the influence of the index of economic efficiency of the intensification of the production of individual crop on the level of their profitability was evaluated. It was established that this rela was non-linear for wheat and sunflower, and linear for grain corn. The practical significance of the obtained results is that the optimal values of the index of economic efficiency and production intensification were determined for sunflower and wheat.
Keywords: costs; economic efficiency; law of diminishing returns; profitability; production intensity; crop products; international markets